Evolution of the structure and function of vertebrate brain gonadotropin-releasing hormone - Powell, R C (Division of Chemical Pathology, 2018)
In this study, the structure and function of gonadotropin-releasing hormone (GnRH) in different vertebrate species, in the classes Aves, Reptilia and Pisces was investigated. Acetic acid extracts were subjected to gel filtration chromatography and semipreparative high performance liquid chromatography (HPLC) to partially purify the GnRHs. The GnRH immunoreactivity was then characterized by analytical HPLC, and by assaying HPLC fractions by radioimmunoassay with region-specific antisera generated against mammalian GnRH, Gln⁸-GnRH and Trp⁷,Leu⁸-GnRH and assessing luteinizing hormone (LH)-releasing activity of fractions in a chicken dispersed anterior pituitary cell bioassay. Five GnRH molecular forms have thusfar been structurally characterized in vertebrate brain. In mammals a GnRH with the structure pGlu-His-Trp-Ser-Tyr-Gly-Leu-Arg-Pro-Gly-NH₂ has been demonstrated in the hypothalamus (Matsuo et al., 1971; Burgus et al., 1972). Gln⁸-GnRH and His⁵,Trp⁷,Tyr⁸-GnRH were present in chicken hypothalamus (King and Millar, 1982a, 1982c; Miyamoto et al., 1983, 1984), Trp⁷,Leu⁸-GnRH in salmon brain (Sherwood et al., 1983) and Tyr³,Leu⁵,Glu⁶,Trp⁷,Lys⁸-GnRH in lamprey brain (Sherwood et al., 1986). In ostrich (Struthio camelus) hypothalamus two GnRHs with identical properties to Gln⁸-GnRH and His⁵,Trp⁷,Tyr⁸-GnRH have been demonstrated, as well as four other LR-releasing factors with different chromatographic and immunological properties to any of the known naturally-occurring GnRHs. Since Gln⁸-GnRH and His⁵,Trp⁷,Tyr⁸-GnRH were also present in chicken hypothalamus it appears likely that these two GnRHs occur in all birds. In alligator (Alligator mississippiensis) brain only two GnRHs were detected. These forms co-eluted with Gln⁸-GnRH and His⁵,Trp⁷,Tyr⁸-GnRH in two HPLC systems. They cross-reacted similarly to the two synthetic peptides with antisera directed against mammalian GnRH and Gln⁸-GnRH and released LH from chicken dispersed anterior pituitary cells in a similar manner to the synthetic peptides. The Archosaurs (alligators and crocodiles) are believed to be closely related to birds and therefore it seems likely that they should have identical GnRHs. In skink (Calcides ocellatus tiligugu) brain one GnRH, which co-eluted with His⁵,Trp⁷,Tyr⁸-GnRH, was demonstrated. Two other lizards (Cordylis nigra and Pordarcis s. sicula) have been studied (Powell et al., 1985; R.C. Powell, G. Ciarcia, V. Lance, R.P. Millar and J.A. King, submitted). In c. nigra four immunoreactive GnRHs were detected, two of which co-eluted released chicken LH similarly to, Trp⁷,Leu⁸-GnRH and with, and His⁵,Trp⁷,Tyr⁸-GnRH. In P. s. sicula a GnRH molecular form similar to Trp⁷,Leu⁸-GnRH occurred as well as two novel GnRHs. It thus appears that Gln⁸-GnRH does not occur in lower reptiles, but His⁵,Trp⁷,Tyr⁸-GnRH and/or Trp⁷,Leu⁸-GnRH do. His⁵,Trp⁷,Tyr⁸-GnRH appears to he a widespread GnRH, occurring in vertebrates as diverse as birds and elasmobranch fish. In dogfish (Poroderma africanum) brain seven factors, which stimulated release of LH from chicken dispersed anterior pituitary cells, were separated on analytical HPLC. Two of these factors were partially characterized as Trp⁷,Leu⁸-GnRH and His⁵,Trp⁷,Tyr⁸-GnRH. Three of the other forms cross-reacted with GnRH antisera, but appear to be novel GnRHs. In teleost (Coris julis) brain two GnRHs similar to Trp⁷,Leu⁸-GnRH and His⁵,Trp⁷,Tyr⁸-GnRH were present. These two GnRHs therefore appear to occur in both fish species studied. Trp⁷,Leu⁸-GnRH is widespread amongst teleost fish (Jackson and Pan, 1983; Sherwood et al., 1983; Breton et al., 1984; Sherwood et al., 1984; King and Millar, 1985). From these data it seems evident that the mammalian GnRH molecular form occurs only in mammals and amphibians, Gln⁸-GnRH in birds and higher reptiles, and Trp⁷,Leu⁸-GnRH in gnathostomes. His⁵,Trp⁷, Tyr⁸-GnRH appears to he present in numerous different vertebrates. Tyr³,Leu⁵,Glu⁶,Trp⁷,Lys⁸-GnRH has thus far only been detected in lamprey brain. A number of novel GnRHs, whose structures have not been elucidated are present.